2007
DOI: 10.1021/ci600410m
|View full text |Cite
|
Sign up to set email alerts
|

3D-Pharmacophore Models for Selective A2Aand A2BAdenosine Receptor Antagonists

Abstract: Three-dimensional pharmacophore models were generated for A2A and A2B adenosine receptors (ARs) based on highly selective A2A and A2B antagonists using the Catalyst program. The best pharmacophore model for selective A2A antagonists (Hypo-A2A) was obtained through a careful validation process. Four features contained in Hypo-A2A (one ring aromatic feature (R), one positively ionizable feature (P), one hydrogen bond acceptor lipid feature (L), and one hydrophobic feature (H)) seem to be essential for antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Interestingly, none of the tested compounds displayed binding at the A 2B AR. Consequently, selectivity of A 2A over A 2B , which is not considered trivial, [28] was reached. The same holds true for compounds with affinity for A 1 , where selectivity over A 2B was (unintentionally) reached.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, none of the tested compounds displayed binding at the A 2B AR. Consequently, selectivity of A 2A over A 2B , which is not considered trivial, [28] was reached. The same holds true for compounds with affinity for A 1 , where selectivity over A 2B was (unintentionally) reached.…”
Section: Discussionmentioning
confidence: 98%
“…Synthesis of thiazolotriazolopyrimidine compounds (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) has been carried out according to Scheme 1. Concisely, the reaction of substituted isothiocyanate, triethylamine, sulfur and malononitrile was carried at 0-5°C for 1 h, then at room temperature for an hour to give the carbonitrile compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Synthesismentioning
confidence: 99%
“…To explicate the interaction of thiazolotriazolopyrimidine derivatives (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) (F168, E169), ECL3 (H 264, W268), TM5 (M174, M177) and TM6 (W246, L249, N253) domains. Docking simulation results showed that thiazolotriazolopyrimidine derivatives (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and SCH58261 shared a similar binding motif inside the transmembrane (TM) region and extracellular loops of the human A 2A R similar to the co-crystallized ZM241385.…”
Section: Molecular Docking Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be used in virtual screening to identify potential molecules, predict the activity of the newly synthesized compound before animal experiment; or understand the possible mechanism of action 21,22 . In the current study, an attempt was made to identify the pharmacophore hypothesis using the …”
mentioning
confidence: 99%